2007
DOI: 10.1029/2007jd008649
|View full text |Cite
|
Sign up to set email alerts
|

Charging state of the atmospheric nucleation mode: Implications for separating neutral and ion‐induced nucleation

Abstract: [1] One way of getting information about the relative roles of neutral and ion-induced nucleation in the atmosphere is to measure the charging state of aerosol particles, i.e., the extent by which the charged fraction of aerosol particles differs from the corresponding equilibrium charged fraction. By using a theoretical approach, we investigated how the charging state of a growing nucleation mode behaves under different atmospheric conditions. We found that the time evolution of the nuclei charging state is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 48 publications
4
63
0
Order By: Relevance
“…The field measurements brought plenty of new insight into the role of ions in atmospheric nucleation Kerminen et al, 2007;Gagné et al, 2008Gagné et al, , 2010Manninen et al, 2010;Mirme et al, 2010;Boulon et al, 2010). The contribution of charged particles to the total formation rate of 2-nm particles was usually found to be well below 10 %, but it showed substantial temporal variability both during a nucleation event and between the different event days.…”
Section: Atmospheric Nucleation Mechanismmentioning
confidence: 99%
“…The field measurements brought plenty of new insight into the role of ions in atmospheric nucleation Kerminen et al, 2007;Gagné et al, 2008Gagné et al, , 2010Manninen et al, 2010;Mirme et al, 2010;Boulon et al, 2010). The contribution of charged particles to the total formation rate of 2-nm particles was usually found to be well below 10 %, but it showed substantial temporal variability both during a nucleation event and between the different event days.…”
Section: Atmospheric Nucleation Mechanismmentioning
confidence: 99%
“…Possible reasons for the absence of charged nucleation-mode particles was that the nucleation took place mostly via a neutral pathway, and the nucleated particles grew so rapidly that they did not get detectable amount of charge until reaching larger sizes (e.g. Kerminen et al, 2007;Leppä et al, 2009). This is very important from the point of view of field event classification: if based on sole ion size distribution measurements, events classified as Aitken events could, in fact, be typical bananas for neutral particles.…”
Section: Self-ending Events -Bananas and Sticksmentioning
confidence: 99%
“…Since particles nucleate below the limit of detection the charged fraction may change from the time of nucleation and until detection. Kerminen et al (2007) described how the charged fraction of a particle population evolves with growth and found that it is dependent on two factors: the cluster ion concentration and the growth rate of the population (corresponding to the amount of condensable gases) such that at high ion concentrations and/or low growth rates the information on the original charging state may be lost when the particles are detected. If the electron can be ejected from a cluster due to the release of e.g.…”
Section: Charged Fractionmentioning
confidence: 99%